Fenomena Praktik Penghindaran Pajak Saat Pandemi Covid-19 Pada Perusahaan Property Dan Real Estate - Fahrul Adhitya Pradana; Sartika Wulandari (Department of Accounting, Faculty of Economics & Business, 2023)
During the Covid-19 pandemic, Indonesia's tax revenues decreased due to weak economic conditions. The government seeks to increase economic activity by providing tax incentive programs to companies as affected taxpayers. However, companies take advantage of the program to carry out tax planning with tax avoidance. The purpose of this study is to analyze the factors that influence tax evasion in property and real estate companies during the Covid 19 pandemic which are listed on the Indonesia Stock Exchange (IDX). This study uses quantitative research. The population of this study are property and real estate companies listed on the IDX. The sampling technique used purposive sampling. The data in this study is secondary data obtained from the IDX. The data used in this study amounted to 78 data. The data analysis method uses panel data regression analysis with Eviews 12 software. The independent variables in this study are institutional ownership, profit levels, firm size and fixed asset intensity. In this study, the results were obtained that institutional ownership had a significant influence on tax avoidance in property and real estate companies during the Covid-19 pandemic. Meanwhile, profit levels, company size and fixed asset intensity did not have a significant effect on tax evasion in property and real estate companies during the Covid-19 pandemic.